Quickgram for Facilitating the Students' Creative Writing Tasks - Rayinda Eva Rahmah (Universitas Muhammadiyah Semarang, 2018)
Creativity has been referred to think outside the box. We commonly view creativity as creating something by experimenting in terms of great pieces of art, literature, drama or music. So, good teachers should pay close attention to the students‟ creative skills in order to performing the foreign language learning. In addition to the digital era, there are many various ways that can be used by teachers to engage students‟ creativity. Exploring mobile applications and integrating social media are the potentials for learning activities. This is because the students have already been familiar with a number of applications for everyday use. Furthermore, the mobile learning apps can facilitate to create windows of opportunity for being creative, flexible, and improvised target language. Thus, this paper focuses on the use of mobile apps namely Quik and Instagram to facilitate the students‟ creative writing tasks. This concept article will how Quik and Instagram are integrated to facilitate creative writing task. Therefore, this study sought to answer the two research questions; (i) How Quik is created and integrated to Instagram and (ii) What are the students‟ perceptions towards the use of Quikgram for facilitating their creative writing task.